2023
DOI: 10.1021/acs.molpharmaceut.3c00600
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Amifostine in Radiation Protection: Administration and Delivery

Lihua Ji,
Pengfei Cui,
Shuwen Zhou
et al.

Abstract: Amifostine (AMF, also known as WR-2721) is the only approved broad-spectrum small-molecule radiation protection agent that can combat hematopoietic damage caused by ionizing radiation and is used as an antitumor adjuvant and cell protector in cancer chemotherapy and radiotherapy. Amifostine is usually injected intravenously before chemotherapy or radiotherapy and has been used in the treatment of head and neck cancer. However, the inconvenient intravenous administration and its toxic side effects such as hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 90 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…However, various chemical radioprotective agents are not suitable for long-term administration due to their severe side effects. 13,14 Recent studies showed that natural radioprotective agents such as polysaccharides, polyphenols, alkaloids and saponins have attracted much attention. Development of new natural radioprotective agents from natural products has gradually become a hot spot for scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…However, various chemical radioprotective agents are not suitable for long-term administration due to their severe side effects. 13,14 Recent studies showed that natural radioprotective agents such as polysaccharides, polyphenols, alkaloids and saponins have attracted much attention. Development of new natural radioprotective agents from natural products has gradually become a hot spot for scientific research.…”
Section: Introductionmentioning
confidence: 99%